Our City is Our Responsibility: Improving the Quality of Bandung’s City Open Space through Community Participation - Yosita, Lucy -; Busono, Rr. Tjahyani; Surasetja, R. Irawan; Hartati, Rd. Diah Sri (Universitas Pendidikan Indonesia, 2019)
This research analysis the usage of various open spaces in Bandung City, and identifies influence of community participation on toward design of open spaces in local area in Bandung. Bandung get 2 times of Adipura Charter Again in 2015, 2016, 2017. The result of analysis indicates City Park as one of central open space in Bandung has been changing in design to be more green, comfortable, and complete with various landscape furniture, and encourage various activities than before. The design of City Park is also impressing to design of several local open spaces as product of PIPPK program, as one of the Mayor of Bandung program to developing Bandung City since 2015-now. Open spaces on local area for example in a village or district, is vary from : court yard, sport field, children playground, and garden as product of community participation. City parks in Bandung is one of the elements that pretty much changed in the last 3 years, in addition to other changes such as : bureaucratic reform, venture capital for the marginalized, and contribution of community by participatory planning, etc. From quantitative analysis the activity value is 93,39%, so it could be conclude that community ’s participation level is good and also the corruption level has been declined. But it is should be needed about increasing allocation for training sector which still on 5,08 % from tottaly fund.